Effects of installing height-adjustable standing desks on daily and domain-specific duration of standing, sitting, and stepping in 3rd grade primary school children - Sprengeler, Ole; Hebestreit, Antje; Gohres, Hannah; Bucksch, Jens; Buck, Christoph (Frontiers in Public Health, 2020)
Background: Aim of this intervention study was to evaluate whether availability of standing desks in classrooms may reduce sitting time and enhance standing and stepping time during lessons and breaks. We evaluated if differences in standing desk use were explained by physical fitness (PF) levels of children and if standing desk use during school hours affected leisure time activity after school. Methods: To assess sitting, standing and stepping during a typical school week in 3rd grade primary school children (N=52), activPAL monitors were used at baseline: T0, 1st follow-up: T1 and 2nd follow-up: T2. At baseline, PF was measured using the standing long jump and the 6-min jog-walk to assign children as having low PF (LPF) or high PF (HPF). Standing desks were assigned randomly to intervention and control groups at T1 (group 1) and T2 (group 2) with a cross-over design. Changes of sitting, standing and stepping were later analyzed to investigate intervention effects at follow-up, using used linear mixed models. Results: At baseline, children spent about 60% and 30% of time sitting during lessons and breaks, respectively. After installing standing desks (T1), significantly lower proportions of sitting were observed in the intervention group (-13.1%, 95%-CI: -20.5; -5.72) and the control group (-9.78%, 95%-CI: -17.3; -2.28). Compared to the baseline measurement (T0), lower proportions of sitting were particularly expressed during school breaks in the intervention groups at T1 (-10.3%, 95%-CI: -16.4; -4.25) and T2 (-8.59%, 95%-CI: -15.2; -1.94). In general, children with higher physical fitness were less sedentary and more active, but intervention effects were not affected by fitness levels. Conclusion: Standing desks provide an opportunity to reduce sedentary time during lessons and breaks at school, but do not directly increase PA of high intensity such as stepping in primary school children with high and low fitness levels as well. Future studies should consider potential bandwagon effects caused by structural interventions.